Hubungan Ketersediaan Sarana dan Prasarana di Sekolah dengan Motivasi Belajar Siswa Kelas V SD Inpres 12/79 Lonrae - rosmalah rosmalah; makmur nurdin; Aifah Abdul Salam (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The problem in this study is the lack of utilization of the availability of facilities and infrastructure in schools so that it affects students' learning motivation. This research is a correlational quantitative research that aims to determine the relationship between the availability of facilities and infrastructure in schools with the learning motivation of fifth grade students of SD Inpres 12/79 Lonrae. The research data were obtained by distributing questionnaires to students. The results showed that there was a significant relationship between the availability of facilities and infrastructure in schools with the learning motivation of fifth grade students at SD Inpres 12/79 Lonrae with a value of (3.79661) greater (>) value (1.66660) which means H0 is rejected and H1 is accepted. Based on the results of the study, it can be concluded that the availability of facilities and infrastructure in schools will have an impact on students' learning motivation. So the better the availability of facilities and infrastructure in schools, it will increase student learning motivation. From these conclusions, the impact resulting from this study is known that the availability of facilities and infrastructure in schools will increase students' learning motivation.